The Effect of Audit Fee and Audit Firm Size on Earnings Management - GAO, HANJI (2017)
Earnings are the most important number in financial reporting and they can provide information that is useful to managers and investors. However, in order to show good performance of companies, managers always manage earnings to provide untrue financial reporting in order to maximum their private interest. This can reduce earnings quality and damage shareholders also investors’ benefits. In this case, audit plays a vital role in constrain earnings management, which can provide independent assurance of the credibility of financial information and contribute to efficient function of capital market allocation. Among audit services, audit fee and audit firm size are widely focused by investors and regulators.